Linear Kalman filter for dead time affected measurement signals implemented in a small scale automated guided vehicle - Lütteke, Felix; Franke, Jörg (Advances in Intelligent Systems and Computing, 2013)
This paper describes an efficient way to calculate state estimations with a linear Kalman filter, if the measurement signal is subject to a fix dead time. In addition the presented solution can handle measurement signals with arbitrarily high sample times. After the derivation of the algorithm an application with high measurement signal dead time is explained. Finally a simulation depicts the result of the algorithm being implemented on the described application. © 2013 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-07
Keywords: AGV; dead time; State estimation